Теоретичне обґрунтування для практичної реалізації аналітичного комп’ютерного побудування динамічних рівнянь в псевдокоординатах керованого польоту БПЛА - Андрєєв, Юрій Михайлович; Лавінський, Денис Володимирович; Дружинін, Євген Іванович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Стаття окреслює важливі питання теоретичного підґрунтя для керування безпілотними літальними апаратами (БПЛА). Актуальність теми статті ґрунтується на великому попиті до застосування БПЛА у різних сферах. Методи керування повинні базуватись на відповідних алгоритмах розв’язання задач динаміки польоту БПЛА. У статті наведено алгоритм для використання в системах комп’ютерної алгебри автоматичного побудування рівнянь динаміки дискретних механічних систем в аналітичній формі. Це обумовлено необхідністю проведення розрахунків динаміки, зокрема, систем БПЛА, структура механічних моделей яких можуть суттєво відрізнятися. Тому потрібні реалізації алгоритмів, які за формальним описом механічної моделі на формульному рівні, будують відповідні рівняння і проводять розрахунки модельованого руху систем з просторовим рухом. Спочатку докладно виводяться рівняння динаміки дискретних моделей з урахуванням фундаментального принципу механіки – загального варіаційного рівняння. Отримано рівняння динаміки в узагальнених координатах у векторно-матричному вигляді, зручному для комп'ютерної реалізації. Пояснюється принципова відмінність уявлення механічного стану систем в узагальнених та псевдо(квазі)координатах. The article outlines important issues of the theoretical basis for controlling unmanned aerial vehicles (UAVs). The relevance of the topic of the article is based on the great demand for the use of UAVs in various fields. Control methods should be based on appropriate algorithms for solving UAVs flight dynamics problems. The article has developed an algorithm for creating in computer algebra systems the automatic calculation of the dynamics of discrete mechanical systems in an analytical form. This is due to the need to carry out the development of dynamics, structure, systems of UAVs, the structure of mechanical models of which can be significantly modified. Therefore, there is a need for implementation of algorithms, such as a formal description of the mechanical model on the formula level, there will be similar levels and carry out the development of the modeled structure of systems with a spacious flow. The dynamics of discrete models are immediately clearly demonstrated in accordance with the fundamental principle of mechanics – the fundamental variational equation. The alignment of dynamics in coordinated coordinates has been extracted from a vector-matrix view, manual for computer implementation. The principle of the validity of the manifestation of the mechanical state of systems in formal and pseudo (quasi) coordinates is explained. Based on the principle of differentiation of functions of localized coordinates behind pseudo-coordinates, by replacing the formulas for variation of localized coordinates, the normalized speeds of which can be expressed through pseudo-coordinates, dynamic coordinates are derived at pseudo-coordinates.
Theoretical justification for the practical implementation of analytical computer construction of dynamic equations in pseudocoordinates of controlled UAV flight
Keywords: рівняння динаміки у псевдокоординатах; рівняння динаміки в узагальнених координатах; комп'ютерна алгебра; керований політ БПЛА; equalization of dynamics in pseudo-coordinates; equalization of dynamics in real coordinates; computer algebra; UAV flight control